Worldwide Bibliometric Analysis of Antibiotic Resistance Research Trends - Amukti, Danang Prasetyaning; Pratami, Ria Indah; Kaffah, Silmi; Ningsih, Novita Fitria; Evelin; Nurdevi, Aldise Indah; Liani, Fega; Panduwinata, Revina; Nurshintya, Agnes; Andre, Muhamad; Nurfaizah, Eka (Biomedical Journal of Indonesia, 2025)
Introduction. Antibiotic resistance (AR) is a critical issue in global health, characterized by the increasing number of resistant pathogens that threaten the effectiveness of infection therapy. Although there has been a significant increase in the number of scientific publications related to AR, there are not many studies that systematically map the dynamics and direction of global research. This study aims to evaluate the global trend of antibiotic resistance research in the period 2022–2025 through a bibliometric approach. Methods. This is a quantitative bibliometric study with a descriptive design. Data were taken from 1,845 indexed international scientific sources, covering 18,786 documents. The analysis was carried out using the Bibliometrix R-package , focusing on publication growth, scientific collaboration, dominant keywords, and identification of the most contributing authors, institutions, and countries. Results. The study showed that despite a -28.01% decline in the annual publication growth rate, research volume remained high, with 27.62% cross-border collaboration and 87,959 authors involved. China and the United States dominated both in terms of publications and citations, while frequent keywords reflected a laboratory approach and focus on major pathogens. The most influential articles were published in leading journals such as The Lancet, Gut, and Clinical Infectious Diseases. Conclusion. This study confirms that antibiotic resistance remains a major focus of the global scientific community, characterized by extensive, collaborative, and evidence-based research activities. These findings provide an important scientific basis for designing more effective, adaptive, and sustainable AR research and policy strategies at the global level.